Genomic Analysis and Stability Evaluation of the Phenol-Degrading Bacterium Acinetobacter sp. DW-1 During Water Treatment - Gu, Qihui; Chen, Moutong; Zhang, Jumei; Guo, Weipeng; Wu, Huiqing; Sun, Ming; Wei, Lei; Wang, Juan; Wei, Xianhu; Zhang, Youxiong; Ye, Qinghua; Xue, Liang; et al. (Frontiers in Microbiology, 2021)
Phenol is a toxic organic molecule that is widely detected in the natural environment, even in drinking water sources. Biological methods were considered to be a good tool for phenol removal, especially microbial immobilized technology. However, research on the “seed” bacteria along with microbial community analysis in oligotrophic environment such as drinking water system has not been addressed. In this study, Acinetobacter sp. DW-1 with high phenol degradation ability had been isolated from a drinking water biofilter was used as seeded bacteria to treat phenol micro-polluted drinking water source. Meanwhile, the whole genome of strain DW-1 was sequenced using nanopore technology. The genomic analysis suggests that Acinetobacter sp. DW-1 could utilize phenol via the β-ketoadipate pathway, including the catechol and protocatechuate branches. Subsequently, a bio-enhanced polyhedral hollow polypropylene sphere (BEPHPS) filter was constructed to investigate the stability of the seeded bacteria during the water treatment process. The denatured gradient gel electrophoresis (DGGE) profile and the quantification of phenol hydroxylase gene results indicate that when the BEPHPS filter was operated for 56 days, Acinetobacter sp. was still a persistent and competitive bacterium in the treatment group. In addition, 16S rRNA gene amplicon sequencing results indicate that Acinetobacter sp., as well as Pseudomonas sp., Nitrospira sp., Rubrivivax sp. were the predominant bacteria in the treatment group, which were different from that in the CK group. This study provides a better understanding of the mechanisms of phenol degradation by Acinetobacter sp. DW-1 at the gene level, and provides new insights into the stability of seeded bacteria and its effects on microbial ecology during drinking water treatment.